KEPENTINGAN INDONESIA MERATIFIKASI MULTILATERAL CONVENTION ON MUTUAL ADMINISTRATIVE ASSISTANCE IN TAX MATTERS(MAC)TAHUN 2011 - Novitasari "; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Transactions between countries raises tax issues (tax matters) caused by the taxpayers who are absent from duty, it should be regulated and agreed to support the economy and trade of a country. International tax policies are needed to regulate the right of taxation prevailing in a country. Therefore, the OECD formulated the MAC to resolve the tax matters. Indonesia ratified the MAC from the OECD because Indonesia wants to get joint administrative assistance in dealing with tax matters. The method used in this research is qualitative research. Data obtained data derived from books, journals, theses, articles, websites and other resources related to the research. The research focus is the interests of Indonesia ratified the MAC in 2011. This study uses the theory of Internal - External Setting and National Interest. This study uses the MAC to increase foreign exchange. Indonesia ratified the MAC in order to receive administrative assistance in dealing with tax matters along with other countries. Indonesia received assistance information exchange, tax collection and abroad, as well as increased cooperation in the field more.Keywords : Tax matters, National interest, administrative assistance